Contamination of aflatoxin B1, deoxynivalenol and zearalenone in feeds in China from 2021 to 2024 - Meng Liu; Zhiyuan Xia; Yu Zhang; Rengui Yang; Weicai Luo; Lijia Guo; Ying Liu; Dessalegn Lamesgen; Hua Sun; Jiangfeng He; Lvhui Sun (Journal of Animal Science and Biotechnology)
Abstract Background This study was carried out to investigate the individual and combined contamination of aflatoxin B1 (AFB1), deoxynivalenol (DON), and zearalenone (ZEN) in feeds in China between 2021 and 2024. A total of 23,003 feed samples, including 17,489 feedstuff samples and 5,514 complete feed samples, were collected from different provinces of China for mycotoxin analysis. Results The analyzed mycotoxins displayed considerably high contamination in the feed samples, with the individual contamination of AFB1, DON, and ZEN were 20.0%–100%, 33.3%–100%, and 85.0%–100%, respectively. The average concentrations of AFB1, DON, and ZEN were 1.2–728.7 μg/kg, 106–8,634.8 μg/kg, and 18.1–3,341.6 μg/kg, respectively. Notably, the rates over China’s safety standards for AFB1, DON, and ZEN in raw ingredients were 9.7%, 2.7%, and 15.7%, respectively. Meanwhile, 3.5%, 1.1%, and 8.7% of analyzed complete feeds exceeded China’s safety standards for AFB1, DON, and ZEN, respectively. Moreover, the co-contamination rates of AFB1, DON, and ZEN in more than 70% of raw ingredients and 87.5% of complete feed products were 60.0%–100% and 61.5%–100%, respectively. Conclusion This study reveals that the feeds in China have commonly been contaminated with AFB1, DON, and ZEN alone and their combination during the past four years. These findings highlight the significance of monitoring mycotoxin contaminant levels in domestic animal feed and the importance of carrying out feed administration and remediation strategies for mycotoxin control.